Time-course Comparison of Xenobiotic Activators of CAR and PPARα in Mouse Liver - Ross, Pamela K. (2008)
Constitutive androstane receptor (CAR) and peroxisome proliferator activated receptor (PPAR)α are transcription factors known to be primary mediators of liver effects, including carcinogenesis, by phenobarbital-like compounds and peroxisome proliferators, respectively, in rodents. Many similarities exist in the phenotypes elicited by these two classes of agents in rodent liver, and we hypothesized that the initial transcriptional responses to the xenobiotic activators of CAR and PPARα will exhibit distinct patterns, but at later time-points these biological pathways will converge. In order to capture the global transcriptional changes that result from activation of these nuclear receptors over a time course in the mouse liver, microarray technology was used. First, differences in basal expression of liver genes between C57Bl/6J wild-type and Car-null mice were examined and 14 significantly differentially expressed genes were identified. Next, mice were treated with phenobarbital (100 mg/kg by gavage for 24 hrs, or 0.085% w/w diet for 7 or 28 days), and liver gene expression changes with regards to both time and treatment were identified. While several pathways related to cellular proliferation and metabolism were affected by phenobarbital in wild-type mice, no significant changes in gene expression were found over time in the Car-nulls. Next, we determined commonalities and differences in the temporal response to phenobarbital and WY-14,643, a prototypical activator of PPARα. Gene expression signatures from livers of wild-type mice C57Bl6/J mice treated with PB or WY-14,643 were compared. Similar pathways were affected by both compounds; however, considerable time-related differences were present. This study establishes common gene expression fingerprints of exposure to activators of CAR and PPARα in rodent liver and demonstrates that despite similar phenotypic changes, molecular pathways differ between classes of chemical carcinogens.